DEVELOPMENT OF AN EDUCATIONAL MODULE FOR INTRODUCING THE BRUBUH TRADITION TO THE YOUNGER GENERATION - Muhammad Fajri Saptaji; Septiyana Baroroh; Nanang Slamet Riyadi (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Local wisdom represents a form of ecological knowledge that has developed through long-term interactions between communities and their natural environments. However, its existence is increasingly threatened by modernization and the limited integration of indigenous knowledge into formal education. One such form of Javanese local wisdom is the Brubuh tradition, a traditional wood-cutting practice regulated by the seasonal calendar system known as Pranata Mangsa. This study aims to develop an educational module based on the Brubuh tradition and the Pranata Mangsa system and to analyze its feasibility and practicality as an integrative learning resource for younger generations. The research employed a Research and Development (R&D) approach adapted from the Borg and Gall model. The research stages included a preliminary study through literature review, interviews, and field observations; module drafting; expert validation involving subject matter experts, instructional design experts, and local cultural practitioners; and limited field testing with students. The findings indicate that the Brubuh tradition embodies strong ecological and material rationality that aligns with modern scientific principles, particularly regarding the influence of moisture content on the physical and mechanical properties of wood. The developed module was evaluated as valid and practical, with student responses reaching an achievement level of 89%, categorized as very good. The integration of local wisdom into the educational module effectively enhanced students’ conceptual understanding, ecological awareness, and appreciation of cultural heritage. This study contributes to the development of contextual learning materials grounded in ethnoscience and offers prospects for applying similar modules based on other forms of local wisdom to support sustainable education and cultural preservation. ABSTRAK Kearifan lokal merupakan bentuk pengetahuan ekologis yang berkembang melalui interaksi panjang antara masyarakat dan lingkungannya, namun keberadaannya semakin terancam oleh modernisasi dan minimnya integrasi dalam pendidikan formal. Salah satu kearifan lokal masyarakat Jawa adalah tradisi Brubuh, yaitu praktik penebangan kayu yang diatur berdasarkan sistem kalender musiman Pranata Mangsa. Penelitian ini bertujuan untuk mengembangkan modul edukasi berbasis tradisi Brubuh dan Pranata Mangsa serta menganalisis kelayakan dan kepraktisannya sebagai sumber belajar integratif bagi generasi muda. Penelitian menggunakan pendekatan Research and Development (R&D) dengan adaptasi model Borg dan Gall. Tahapan penelitian meliputi studi pendahuluan melalui kajian literatur, wawancara, dan observasi lapangan; penyusunan draf modul; validasi oleh ahli materi, ahli desain pembelajaran, dan praktisi budaya; serta uji coba terbatas kepada peserta didik. Hasil penelitian menunjukkan bahwa tradisi Brubuh mengandung rasionalitas ekologis dan material yang selaras dengan konsep ilmiah modern, khususnya terkait pengaruh kadar air terhadap sifat fisik dan mekanik kayu. Modul yang dikembangkan dinilai layak dan praktis, dengan respons peserta didik mencapai tingkat ketercapaian sebesar 89% pada kategori sangat baik. Integrasi kearifan lokal ke dalam modul pembelajaran terbukti mampu meningkatkan pemahaman konsep, kesadaran ekologis, serta apresiasi terhadap warisan budaya. Penelitian ini berkontribusi pada pengembangan bahan ajar kontekstual berbasis etnosains dan membuka peluang penerapan modul serupa pada kearifan lokal lain sebagai upaya pendidikan berkelanjutan dan pelestarian budaya.